2017
DOI: 10.1080/00325899.2017.1335956
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effect of high-energy milling time of Ti6Al4V biomaterial on the wear performance in the simulated body fluid environment

Abstract: In this study, the effect of milling time on wear behaviour of the Ti6Al4V alloy produced with the high-energy milling method was investigated. The Ti6Al4V alloy was milled at five different milling times in a mechanical alloying device. The milled powders were cold-pressed under 620 MPa pressure, sintered at 1300°C for 2 h and cooled to room temperature in the furnace. The sintered alloys were characterised with SEM, XRD and hardness and density measurements. Wear tests were performed using a pin-on-disc type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As the high-energy milling time increases, V-rich regions (zone shown with 2) in the matrix are observed to decrease (due to the decrease in the average particle size of the powder). This is because decreasing vanadium shows a more homogeneous distribution during the high-energy milling process [15]. Figure 2 shows the XRD results of Ti6Al4V alloys high-energy milled for 15 and 120 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the high-energy milling time increases, V-rich regions (zone shown with 2) in the matrix are observed to decrease (due to the decrease in the average particle size of the powder). This is because decreasing vanadium shows a more homogeneous distribution during the high-energy milling process [15]. Figure 2 shows the XRD results of Ti6Al4V alloys high-energy milled for 15 and 120 min.…”
Section: Resultsmentioning
confidence: 99%
“…A planetary-type mill was used in high-energy milling operations of elemental powders prepared. The powders prepared in the desired chemical composition were high-energy milled in stainless steel milling chamber using five different milling times (15,30,60, 90 and 120 min). One percent ethanol as process control chemical, stainless steel balls 8 mm in diameter, 20:1 ball/powder ratio and 50% chamber fill rate were used to prevent agglomeration during these operations.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that the size of the pores in the microstructure decreased with increasing MA time. A former study reports that the MA time is an effective process parameter for the powder size of the alloy in the MA process [8]. The decrease in the size of powder grains leads to a decrease in the pore size.…”
Section: Methodsmentioning
confidence: 99%
“…The heat-treated specimens were firstly immersed in the solution for 60 min until the open circuit potential (OCP) reached its level. Polarization measurements were performed in a conventional corrosion cell in the SBF (Table 2 [32] ; pH %7.40). Electrochemical impedance spectroscopy (EIS) was conducted in the frequency range of 10 mHz to 100 kHz with a 5 mV amplitude of the alternating current (AC) signal.…”
Section: Methodsmentioning
confidence: 99%